Characterization of a degraded cadmium yellow (CdS) pigment in an oil painting by means of synchrotron radiation based X-ray techniques - Van der Snickt, Geert; Dik, Joris; Cotte, Marine; Janssens, Koen; Jaroszewicz, Jakub; De Nolf, Wout; Groenewegen, Jasper; Van der Loeff, Luuk (Analytical chemistry (Washington), 2009)
On several paintings of James Ensor (1860-1949), a gradual fading of originally bright yellow areas, painted with the pigment cadmium yellow (CdS), is observed. Additionally, in some areas exposed to light, the formation of small white-colored globules on top of the original paint surface is observed. In this paper the chemical transformation leading to the color change and to the formation of the globules is elucidated. Microscopic X-ray absorption near-edge spectroscopy (mu-XANES) experiments show that sulfur, originally present in sulfidic form (S(2-)), is oxidized during the transformation to the sulfate form (S(6+)). Upon formation (at or immediately below the surface), the highly soluble cadmium sulfate is assumed to be transported to the surface in solution and reprecipitates there, forming the whitish globules. The presence of cadmium sulfate (CdSO(4).2H(2)O) and ammonium cadmium sulfate [(NH(4))(2)Cd(SO(4))(2)] at the surface is confirmed by microscopic X-ray diffraction measurements, where the latter salt is suspected to result from a secondary reaction of cadmium sulfate with ammonia. Measurements performed on cross sections reveal that the oxidation front has penetrated into the yellow paint down to ca. 1-2 microm. The morphology and elemental distribution of the paint and degradation product were examined by means of scanning electron microscopy equipped with an energy-dispersive spectrometer (SEM-EDS) and synchrotron radiation based micro-X-ray fluorescence spectrometry (SR micro-XRF). In addition, ultraviolet-induced visible fluorescence photography (UIVFP) revealed itself to be a straightforward technique for documenting the occurrence of this specific kind of degradation on a macroscale by painting conservators.